Sexual Fantasies and Harmful Sexual Interests: Exploring Differences in Sexual Memory Intensity and Sexual Fantasy Characteristics. (June 2023) - Allen, Andrew; Millear, Prudence; McKillop, Nadine; Katsikitis, Mary
The perpetration of harmful sexual behavior is a global concern, with deviant sexual fantasies identified as a prominent etiological risk factor. However, the concepts of state sexual fantasy characteristics (e.g., vividness and emotionality) and associated trait sexual memory intensity have received minimal investigation concerning harmful sexual interests, formulating the impetus for this research. Two online surveys were conducted in community populations. Study 1 ( N  = 414) aimed to validate the psychometric properties of a trait sexual memory intensity scale (SMIS) through principal components analysis, confirmatory factor analysis, and evaluation of concurrent validity. Study 2 ( N  = 820) endeavored to explore associations between state sexual fantasy characteristics and cognitive-behavior variables (e.g., frequency of masturbation to a reported fantasy), and evaluate differences in fantasy characteristics and SMIS scores between participants with and without harmful sexual interests. Collectively, results supported the factor structure, concurrent validity, and internal consistency of the SMIS, while revealing significant associations between the SMIS, sexual fantasy characteristics, and several variables. Significant differences in sexual fantasy characteristics and SMIS scores were evident but variable among harmful sexual interests. Findings encourage the consideration and research of interventions focused on impairing mental imagery and memory in the management of harmful sexual interests.